Quantifying the germination response of Parthenium hysterophorus at various temperatures and water potentials by using population-based threshold model - Afzal, Irfan; Akram, Muhammad; Javed, Talha; Ali, Faryal; Kalaji, Hazem M.; Wróbel, Jacek; Telesiński, Arkadiusz; Mojski, Jacek; Ahmed, Mohamed A. A. (Frontiers in Plant Science, 2022)
Predicting the germination behavior of parthenium weed against different conditions of temperature and osmotic stress is helpful for studying the growth and development history of parthenium in different ecological contexts. Sustainable weed control strategies based on population-based threshold models are profitable tools for crop planting date, herbicide application and tillage operation time. To predict the emergence of parthenium by using thermal time, hydrotime and hydrothermal time analysis, seeds were exposed to varying constant temperatures (5, 10, 15, 20, 25, 30, 35 and 40 °C) and water potentials (-0.25, -0.5, -0.75 and -1.0 MPa) under a controlled environment. Parthenium seeds showed better responses in terms of higher germination percentage and lower germination time at 20 and 25 °C. Use of germination modeling approach proposed the base temperature (7.2 °C), optimum temperature (20 °C) and ceiling temperature (42.8 °C) for this weed. Moreover, germination behavior was also studied at different water potentials under different temperature regimes (10, 20 and 30 °C). Hydrothermal time model predicted higher germination percentages (82.8 and 54.8 %) of parthenium seeds at water potentials from 0 to -0.25 MPa, respectively, under a temperature of 20 °C, and also identified a base water potential (Ψb(50) of -0.54 MPa for germination. In conclusion, the use of hydrothermal time modeling approach is helpful for predicting the emergence response of parthenium in a changing climate and ultimately supportive in time scheduling of parthenium weed management in cropping systems.